2002
DOI: 10.1088/0954-3899/29/1/301
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in precision electroweak physics

Abstract: Developments in precision electroweak physics in the two years since the symposium are briefly summarized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…The difference is mainly due to their use of an earlier estimate [20] ∆α (5) had (M Z ) = 0.02803 ± 0.00065. Gurtu reported that their M H increased to the consistent 88 +60 −37 GeV when they used a newer ∆α (5) had (M Z ) = 0.02755 ± 0.00046 [21] based on the new BES-II e + e − data. group and representations; does not explain charge quantization, the fermion families, or their masses and mixings; has several notorious fine tunings associated with the Higgs mass, the strong CP parameter, and the cosmological constant; and does not incorporate quantum gravity.…”
Section: −32mentioning
confidence: 98%
See 4 more Smart Citations
“…The difference is mainly due to their use of an earlier estimate [20] ∆α (5) had (M Z ) = 0.02803 ± 0.00065. Gurtu reported that their M H increased to the consistent 88 +60 −37 GeV when they used a newer ∆α (5) had (M Z ) = 0.02755 ± 0.00046 [21] based on the new BES-II e + e − data. group and representations; does not explain charge quantization, the fermion families, or their masses and mixings; has several notorious fine tunings associated with the Higgs mass, the strong CP parameter, and the cosmological constant; and does not incorporate quantum gravity.…”
Section: −32mentioning
confidence: 98%
“…• The combination of WNC and WCC data uniquely determined the SU (2) representations of all of the known fermions, i.e., of the ν e and ν µ , as well as the L and R components of the e, µ, τ, d, s, b, u, and c [5]. In particular, the left-handed b was the lower component of an SU (2) doublet, implying unambiguously that the t quark had to exist.…”
Section: Historical Perspectivementioning
confidence: 99%
See 3 more Smart Citations